The Impact of Fish Farmers’ Group Participation on The Catfish Sector Income in Pringsewu District - Putri, Septiyana Nur Fitriyani; Tinaprilla, Netti; Utami, Anisa Dwi (Jurnal Manajemen dan Agribisnis, 2024)
Background: Challenges farmers face such as low bargaining power, difficulty accessing information regarding farming and marketing of production can be overcome if catfish farmers are active in fish farmers’ groups. Fish farming groups were formed to increase their members' farming income, through implementing fisheries businesses supported by infrastructure assistance from the Government. Purpose: This research aims to analyze the role of fish farmers groups towards members, analyze catfish on farm income, and analyze differences in income based on participation in farming groups. Design/methodology/approach: This study used a non-probability sampling method to sample 100 catfish farmers which is divided into 51 members and 49 non-members of the fish farming group. The method used is quantitative analysis using Endogenous Switching Regression (ESR) model analysis. Findings/Result: The results of the research show that the fish farmers group has a sufficient role as a place for teaching and learning, a place for cooperation and production units, and the rho (ρ) value in the ESR model estimation shows that participation in farmers group has a positive impact on the income of members of catfish farming, namely that members' on farm income is greater than the income of random sample individuals and the income of non-members of the fish farmers group.Conclusion: Role and participation in fish farming groups have a positive impact on members' on farm income, namely members' income is greater than non-members, and members' on farm income can increase.Originality/value (State of the art): This research uses exogenous and endogenous variables which together in the ESR method can influence participation decisions in fish farming groups. Research by Mutiara et al. (2023) used a questionnaire to analyze the role of cultivation groups qualitatively, while in the research, apart from using a questionnaire with a Likert scale, empirical evidence was also carried out using the ESR model. Keywords: Analytical Hierarchy Process, corporate sustainability indicators, sustainability practices, performance measurements, PT. Sido Muncul Tbk